2013
DOI: 10.1128/jvi.02714-12
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Treatment Regulates the Humoral Immune Response during Acute Viral Infection

Abstract: Generation of reactive oxygen intermediates (ROI) following antigen receptor ligation is critical to promote cellular responses. However, the effect of antioxidant treatment on humoral immunity during a viral infection was unknown. Mice were infected with lymphocytic choriomeningitis virus (LCMV) and treated with Mn(III)tetrakis(4-benzoic acid)porphyrin chloride (MnTBAP), a superoxide dismutase mimetic, from days 0 to 8 postinfection. On day 8, at the peak of the splenic response in vehicle-treated mice, virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…Recently, it has been observed that parvovirus infection is linked with oxidative stress, and marked enhancement of reactive oxygen/nitrogen species, lipid peroxidation, DNA damage and poor antioxidant reserve (Luo & Qiu, ; Nykky, Vuento, & Gilbert, ; Panda, Patra, Nandi, & Swarup, ). In recent years, emphasis has been given on the antioxidants as the potential drugs of interest for management of viral diseases (Beck, ; Chandrasena et al., ; Crump, Langston, Rajkarnikar, & Grayson, ). A strong association of CPV with oxidative stress suggests incorporation of antioxidants in therapeutic regimen in canine parvoviral diarrhea may help in ameliorating the clinical signs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been observed that parvovirus infection is linked with oxidative stress, and marked enhancement of reactive oxygen/nitrogen species, lipid peroxidation, DNA damage and poor antioxidant reserve (Luo & Qiu, ; Nykky, Vuento, & Gilbert, ; Panda, Patra, Nandi, & Swarup, ). In recent years, emphasis has been given on the antioxidants as the potential drugs of interest for management of viral diseases (Beck, ; Chandrasena et al., ; Crump, Langston, Rajkarnikar, & Grayson, ). A strong association of CPV with oxidative stress suggests incorporation of antioxidants in therapeutic regimen in canine parvoviral diarrhea may help in ameliorating the clinical signs.…”
Section: Introductionmentioning
confidence: 99%
“…Following anti-CD3 or peptide stimulation, ROS including superoxide and hydrogen peroxide, are produced by both CD4 + and CD8 + T cells (30, 31). This production is essential as blocking it with antioxidants decreases the expansion of T and B cells in vitro and in vivo (32, 33). Following ROS production in T and B cells cysteine becomes reversibly oxidized to sulfenic acid (31, 34).…”
Section: Discussionmentioning
confidence: 99%
“…In avian diseases, pathogens are recognised by the innate immune system leading to the production of O 2 − in the phagosome and outside the cells by the process of oxidative or respiratory burst, catalysed by the NADPH oxidase complex (NOX). This process of ROS production is critical to promote cellular responses [7]. The O 2 − , produced by the immune cells, can lead to the formation of other ROS such as HOCl, H 2 O 2 , peroxynitrite (ONOO − ), and OH [20, 22].…”
Section: Reactive Species Oxidative Stress and Antioxidant Systemmentioning
confidence: 99%
“…Production of the ROS from activated innate immune cells such as neutrophils and macrophages is involved in the destruction of microbes/viruses and infected cells by oxidative bursts [6]. These ROS guide the development of adoptive immune responses, including the proliferation of T cells and positive mediation of B cell functions [7, 8].…”
Section: Introductionmentioning
confidence: 99%